Prevalence and Pattern of Birth Defects in a Tertiary Care Hospital in Bangladesh - Akter, Jesmin; Ahammad, Forrukh; Parvin, Rukhsana; Islam, Md Tariqul; Rahman, Md Ashadur; Islam, Md Tajul (Sir Salimullah Medical College Journal, 2022)
Background: Birth Defect is one of the most important causes of neonatal mortality and morbidity worldwide. The pattern and prevalence of Birth Defects may vary overtime or with geographic location. The objective of the study to determine the prevalence and pattern of Birth Defects in live newborn admitted in Hospital. Materials & Methods: This cross-sectional descriptive study was carried in Neonatology and OBS-gynae department of Sir Salimullah Medical college Hospital during the period of July 2016 to December 2019. A total 306 babies with Birth Defects were examined and detailed history for any risk factor was taken. A through physical examination was performed. Confirmation of internal defect was done by various imaging modalities; i.e, radiography, ultrasound, echocardiography and CT scan. A detailed history was taken regarding maternal age, gestational age and previous delivery of abnormal baby. Results: During this period total 27799 was born alive, of which 306 had Birth Defects, the prevalence of Birth Defects was 1.1%. The predominant system involved was Musculoskeletal system (30%) followed by CNS (19%), oro-facial clefts (13%), GIT, CVS, Ear-nosethroat( 7%) and least involved system was urinary system(4%). Talipes was most common one in musculo-skeletal system defect and Anencephaly in CNS defect. Conclusion: Prevalence of Birth Defects is common among newborn admitted in hospital and musculoskeletal system is most commonly affected system. Birth Defects is upcoming issue in current newborn situation which need to be prioritized. Sir Salimullah Med Coll J 2022; 30: 23-28